2010
DOI: 10.1139/g09-100
|View full text |Cite
|
Sign up to set email alerts
|

A candidate gene for choanal atresia in alpaca

Abstract: Choanal atresia (CA) is a common nasal craniofacial malformation in New World domestic camelids (alpaca and llama). CA results from abnormal development of the nasal passages and is especially debilitating to newborn crias. CA in camelids shares many of the clinical manifestations of a similar condition in humans (CHARGE syndrome). Herein we report on the regulatory gene CHD7 of alpaca, whose homologue in humans is most frequently associated with CHARGE. Sequence of the CHD7 coding region was obtained from a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The high number of congenital defects in neonatal NWC has been observed in other studies . The 2 main defects found in this study were, as previously reported, choanal atresia and vulvar deformity . Although choanal atresia can be corrected, this study suggests that the presence of this defect is associated with a poor outcome.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The high number of congenital defects in neonatal NWC has been observed in other studies . The 2 main defects found in this study were, as previously reported, choanal atresia and vulvar deformity . Although choanal atresia can be corrected, this study suggests that the presence of this defect is associated with a poor outcome.…”
Section: Discussionsupporting
confidence: 80%
“…The poor prognosis of NWC with congenital defects could be associated with the purpose of the animals presented. The presence of congenital defects might limit the value of an animal as some defects, like choanal atresia, have been shown to have a genetic component . .…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Surgical correction of choanal atresia has been attempted, but euthanasia should be considered because of the high rate of complications and their effects on quality of life. 38 38 …”
Section: Cardiac Abnormalitiesmentioning
confidence: 99%
“…High frequencies allow only superficial structures to be imaged, but at higher resolution and image quality than those of low frequency. 39 The study was not able to definitively determine the genetic abnormality that causes CA but did sequence the CDH7 gene in alpacas for further study. With large adult camelids, low frequency (4-5 MHz) convex or sector transducers are typically favored for thoracic imaging.…”
Section: Thoracic Ultrasonography (Excluding the Heart)mentioning
confidence: 99%